2017
DOI: 10.1021/acs.iecr.7b03331
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effect of Salinity on the Behavior of Asphaltene Precipitation in the Presence of Emulsified Water

Abstract: Asphaltenes precipitation and deposition is one of the main problems in the petroleum industries which has attracted the attention of many scholars. Precipitation and deposition of asphaltenes can lead to many problems in oil reservoirs such as plugging the pores of the reservoir rocks and changing the wettability of the rocks from water-wet to oil-wet. This ultimately causes a reduction or puts an end to production from reservoirs. Therefore, understanding the factors affecting the formation of asphaltenes pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
39
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 27 publications
9
39
1
Order By: Relevance
“…Also, higher interactions among asphaltene molecules occurred with an increase in the number of free ions and anions in which the stability increased because the asphaltene molecules have multiple active electronegative sites such as -OH, =C=O and =N (Lashkarbolooki et al 2016). These chemical bonds strongly tend to absorb protons, and it is possible for negatively charged asphaltene molecules to be absorbed onto H + ions and become positive loads (Lashkarbolooki et al 2016;Shojaati et al 2017). As a result of low and high pH values, functional groups of asphaltene are charged and result in higher polarity and hydrophilicity that increase the stability.…”
Section: Resultsmentioning
confidence: 99%
“…Also, higher interactions among asphaltene molecules occurred with an increase in the number of free ions and anions in which the stability increased because the asphaltene molecules have multiple active electronegative sites such as -OH, =C=O and =N (Lashkarbolooki et al 2016). These chemical bonds strongly tend to absorb protons, and it is possible for negatively charged asphaltene molecules to be absorbed onto H + ions and become positive loads (Lashkarbolooki et al 2016;Shojaati et al 2017). As a result of low and high pH values, functional groups of asphaltene are charged and result in higher polarity and hydrophilicity that increase the stability.…”
Section: Resultsmentioning
confidence: 99%
“…Another important development in effective utilization of injected water is the addition of salts in low concentrations, in the process called low saline water (LSW) injection. Several studies observed that the injection of low salinity brine helps to achieve higher incremental oil recovery (Al Harrasi et al, 2012;Brady and Krumhansl, 2012;Nasralla and Nasr-El-Din, 2014;Shaddel et al, 2014;Shojaati et al, 2017;Yang et al, 2016). Sharma and Filoco (2000) suggested that the use of low-salinity brine, as connate fluid, alters the wettability of the rock from a water-wet to a mixed-wet surface and contributes to an increase in oil recovery.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, gas injections, including injection of CO 2, can disturb the chemical and thermodynamic balance of crude oil and cause precipitation of asphaltene. Of course, some key factors such as solvent type sample/ precipitant ratio and contact time cannot be ignored in the analysis of the process (David Ting et al, 2013;Ebrahimi et al, 2016;Hammami et al, 2000;Hu and Guo, 2001;Shojaati et al, 2017). Keeping the operational conditions at the level similar to the initial condition is practically impossible and is very difficult and costly work, thus effectual ways should be chosen to solve the problem.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the costs are related to the production of raw materials for inhibitors. Therefore, asphaltene inhibitor should be selected with the optimum concentration (Imanbayev et al, 2017;Mao et al, 2017;Permanyer et al, 2002;Shojaati et al, 2017;Simakov et al, 2015;Smith et al, 2008). Recently researchers have shown that asphaltene acts as a weakly hydrous binder and also as a strong receiver of hydrous bands, which shows that asphaltene is a Lewis base.…”
Section: Introductionmentioning
confidence: 99%